STUDENTS' PERCEPTIONS OF TOTAL PHYSICAL RESPONSE IN LISTENING INSTRUCTION - Kukuh Aldi Rizky; Sultan Baa; Geminastiti Sakkir (Universitas Negeri Makassar, 2026)
This study explored students' perceptions of the Total Physical Response (TPR) method in listening instruction at SMAN 3 Makassar. Using a qualitative descriptive design, six students were purposively selected from different achievement categories to participate in semi-structured interviews following the implementation of TPR activities. The interview data were analyzed using thematic analysis based on the interactive model of Miles, Huberman, and Saldaña. The results revealed six major themes: enjoyable learning experiences, increased classroom interaction, improved understanding of oral instructions, challenges during implementation, enhanced motivation and confidence, and positive attitudes toward future use of TPR. Students perceived that physical movement helped them connect spoken language with meaning, reduced anxiety, and created a more engaging learning environment. The results suggest that TPR provides substantial affective and pedagogical benefits for listening instruction in EFL classrooms.